2023
DOI: 10.1128/aem.01545-22
|View full text |Cite
|
Sign up to set email alerts
|

Viral Preservation with Protein-Supplemented Nebulizing Media in Aerosols

Abstract: We have identified common and inexpensive lab reagents that confer increased aerosol survivability on phi6 and other phages. Our results suggest that soluble protein is a key protective component in nebulizing medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…We posit that the lower airborne RSV viability in all of the tested scenarios may be attributed to the reduced protein concentration. Interestingly, Humphrey et al demonstrated that the addition of bovine serum albumin (BSA) to the suspension medium significantly improved the retrieval of airborne bacteriophages . This finding suggests that proteins might indeed play a vital role in the survival rates of airborne viruses, potentially contributing to the observed U-shaped RH dependence curve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We posit that the lower airborne RSV viability in all of the tested scenarios may be attributed to the reduced protein concentration. Interestingly, Humphrey et al demonstrated that the addition of bovine serum albumin (BSA) to the suspension medium significantly improved the retrieval of airborne bacteriophages . This finding suggests that proteins might indeed play a vital role in the survival rates of airborne viruses, potentially contributing to the observed U-shaped RH dependence curve.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Humphrey et al demonstrated that the addition of bovine serum albumin (BSA) to the suspension medium significantly improved the retrieval of airborne bacteriophages. 51 This finding suggests that proteins might indeed play a vital role in the survival rates of airborne viruses, potentially contributing to the observed U-shaped RH dependence curve. However, further investigations are needed to address this knowledge gap for actual respiratory viruses.…”
Section: Airborne Rsv Viability In Different Static Indoor Air Condit...mentioning
confidence: 94%
“…Aerosol phase virus viability studies were identified in the body of literature as described in detail in the Supporting Information (section S1). The selection of studies was refined by excluding publications that investigated viruses that are structurally dissimilar to model respiratory viruses (influenza A virus and human rhinovirus).…”
Section: Methods and Study Exclusion Criteriamentioning
confidence: 99%
“…Humphrey et al demonstrated that the effects of the composition of the spraying medium alone were sufficient to modify bacteriophage V 10 from the low-viability to the highviability regime, indicating that particle composition can have an important effect on aerostability on short time scales. 54 A further experimental consideration is the precise RH experienced by the particles during the measurement. NaCl, which is present in nearly every spray suspension, experiences state-dependent hysteresis through changing RH.…”
Section: ■ Effect Of Humidity On Viral Viabilitymentioning
confidence: 99%
See 1 more Smart Citation